Progressing the Governance Standards: Role of HR. Issue 4 (October 2019) - Mukherjee, Rachna
Abstract: To have a robust governance standard become a practice in an organisation requires both a lucid stating of the principles and code of conduct along with creating a culture where a respect for these principles is acknowledged and positively reinforced. The human resources team plays a critical role in this scenario by offering a cogent professional conduct template as well as fostering a sustained culture, reflective of this, given the interventions which HR can facilitate across business units and different sets of professional segments.